'We always find things to learn from.' Lessons from the implementation of the global maternal sepsis study on research capacity: a qualitative study - Rachidatou Compaoré; Vanessa Brizuela; Anne M. Khisa; Alejandra López Gómez; Adama Baguiya; Mercedes Bonet; Anna Thorson; Evelyn Gitau; Seni Kouanda (BMC, 2021)
Abstract Background Research capacity strengthening could be an indirect outcome of implementing a research project. The objective of this study was to explore the ability of the global maternal sepsis study (GLOSS), implemented in 52 countries, to develop and strengthen sexual and reproductive health research capacity of local participants in low- and middle- income participating countries. Methods We carried out a qualitative study employing grounded theory in sixteen countries in Africa and Latin America. We used inductive and deductive methods through a focus group discussion and semi-structured interviews for the emergence of themes. Participants of the focus group discussion (n = 8) were GLOSS principal investigators (PIs) in Latin America. Interviewees (n = 63) were selected by the country GLOSS PIs in both Africa and Latin America, and included a diverse sample of participants involved in different aspects of study implementation. Eighty-two percent of the participants were health workers. We developed a conceptual framework that took into consideration data obtained from the focus group and refined it based on data from the interviews. Results Six themes emerged from the data analysis: recognized need for research capacity, unintended effects of participating in research, perceived ownership and linkage with the research study, being just data collectors, belonging to an institution that supports and fosters research, and presenting study results back to study implementers. Research capacity strengthening needs were consistently highlighted including involvement in protocol development, training and technical support, data analysis, and project management. The need for institutional support for researchers to conduct research was also emphasised. Conclusion This study suggests that research capacity strengthening of local researchers was an unintentional outcome of the large multi-country study on maternal sepsis. However, for sustainable research capacity to be built, study coordinators and funders need to deliberately plan for it, addressing needs at both the individual and institutional level.